2016
DOI: 10.1021/acs.jpcc.6b05335
|View full text |Cite
|
Sign up to set email alerts
|

Eu3+-Doped Wide Band Gap Zn2SnO4 Semiconductor Nanoparticles: Structure and Luminescence

Abstract: Figure S1. (a) The diffuse reflectance spectra and (b) plot of [F(R)•hν] 2 vs. photon energy of Zn 2 SnO 4 and Zn 2 SnO 4 :Eu nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 38 publications
0
24
1
Order By: Relevance
“…Consequently, as both of these sites are centrosymmetric, electric dipole transitions ( 5 D0-7 Fj=0,2, only the 5 D0-7 F2 transition is observed in this study) are forbidden and, as such, should not appear in the spectra. As the synthesizing temperature is 900 °C, the fact that the 5 D0-7 F2 electric dipole transition at 615 nm prevails over the 5 D0-7 F1 magnetic dipole transition at 595 nm in the case of Sr2−xEuxZnMoO6 phosphors leads us to the conclusion that the Eu 3+ ions are generally located in a disordered manner in the Sr2−xEuxZnMoO6 powders [27]. The charge-compensating oxygen vacancies surrounding the Eu 3+ ions will lead to the deviation from the point symmetry and relaxation of electric dipole transitions selection rules, with the appearance of the 5 D0-7 F2 transition lines in the spectra [27].…”
Section: Rose the Results Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, as both of these sites are centrosymmetric, electric dipole transitions ( 5 D0-7 Fj=0,2, only the 5 D0-7 F2 transition is observed in this study) are forbidden and, as such, should not appear in the spectra. As the synthesizing temperature is 900 °C, the fact that the 5 D0-7 F2 electric dipole transition at 615 nm prevails over the 5 D0-7 F1 magnetic dipole transition at 595 nm in the case of Sr2−xEuxZnMoO6 phosphors leads us to the conclusion that the Eu 3+ ions are generally located in a disordered manner in the Sr2−xEuxZnMoO6 powders [27]. The charge-compensating oxygen vacancies surrounding the Eu 3+ ions will lead to the deviation from the point symmetry and relaxation of electric dipole transitions selection rules, with the appearance of the 5 D0-7 F2 transition lines in the spectra [27].…”
Section: Rose the Results Inmentioning
confidence: 99%
“…As the synthesizing temperature is 900 °C, the fact that the 5 D0-7 F2 electric dipole transition at 615 nm prevails over the 5 D0-7 F1 magnetic dipole transition at 595 nm in the case of Sr2−xEuxZnMoO6 phosphors leads us to the conclusion that the Eu 3+ ions are generally located in a disordered manner in the Sr2−xEuxZnMoO6 powders [27]. The charge-compensating oxygen vacancies surrounding the Eu 3+ ions will lead to the deviation from the point symmetry and relaxation of electric dipole transitions selection rules, with the appearance of the 5 D0-7 F2 transition lines in the spectra [27]. Additionally, the Eu 3+ luminescent centers contributing to the 5 D0-7 F2 transition line are probably located at the Sr2−xEuxZnMoO6 particle surface or subsurface and will dominate the emission of Sr2−xEuxZnMoO6 phosphors when the synthesizing temperature is 1200 °C [27].…”
Section: Rose the Results Inmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Furthermore, Das et al reported a facile approach to synthesize Zn 2 SnO 4 nanoparticles by a temperature-dependent solid-state reaction. 18 The effect of Bi doping on visible-light absorption and photoluminescence properties of Zn 2 SnO 4 were also studied by Liu et al 19 Recently, room-temperature ferromagnetism was observed in Mn-doped Zn 2 SnO 4 nanowires, which were synthesized by chemical vapor transport in a horizontal tube furnace. Wang et al synthesized pure and Dydoped Zn 2 SnO 4 hollow spheres using the coprecipitation method and showed that their photoluminescence and photocatalytic properties can be improved.…”
Section: Introductionmentioning
confidence: 98%
“…17 Dimitrievska et al synthesized Eu-doped Zn 2 SnO 4 nanoparticles through solid-state reaction method and characterized their optical properties. 18 The effect of Bi doping on visible-light absorption and photoluminescence properties of Zn 2 SnO 4 were also studied by Liu et al 19 Recently, room-temperature ferromagnetism was observed in Mn-doped Zn 2 SnO 4 nanowires, which were synthesized by chemical vapor transport in a horizontal tube furnace. 20 The influence of Co doping on optical and magnetic properties of Zn 2 SnO 4 nanostructures prepared by simple coprecipitation technique was also investigated by Sumithra et al 21 In this work, Zn 2 SnO 4 nanoparticles are doped with silicon to improve their electrical and optical properties.…”
Section: Introductionmentioning
confidence: 98%